Wave climate and energy resources in American Samoa from a 42-year high-resolution hindcast. (July 2023) - García Medina, Gabriel; Yang, Zhaoqing; Li, Ning; Cheung, Kwok Fai; Lutu-McMoore, Elinor
Abstract: This paper presents an analysis of the wave climate and a characterization of the wave energy resources in American Samoa, a U.S. territory covering seven south central Pacific islands and atolls. A numerical wave model based on WAVEWATCH III® and unstructured SWAN was developed, validated, and executed for 1979–2020 to generate a hindcast dataset suitable for resource characterization. Model-data comparisons were performed with measurements collected in situ and from satellite-based altimeters. The model was found to perform well with a bias in significant wave height of −0.14 m and −0.06 m against buoy and altimeters, respectively. The multimodal sea state of American Samoa is investigated by identifying the sources of energy reaching the islands and partitioning the wave spectrum accordingly. The wave resources characterization follows the International Electrotechnical Commission Technical Specifications to be compatible with studies performed for other U.S. regions. The average omnidirectional wave power at 2 km from shore around Tutuila, the main island of American Samoa, is 14 kW/m. Locations east and west of the islands have a more consistent resource throughout the year because the northwest and southwest swells that are dominant during different seasons complement each other. Highlights: A wave model covering the American Samoa EEZ was developed and validated. The first wave resources characterization of American Samoa following international standards. Wave power averages 15 kW/m with a standard deviation of 12 kW/m 2 km from shore. Wave power has low monthly variability on the east and west shores of the main islands.